Feasibility of PET/CT system performance harmonisation for quantitative multicentre Zr-89 studies - Kaalep Andres; Huisman Marc; Séra Teréz Emese; Vugts Danielle; Boellaard Ronald; Kollaborációs szervezet: EARL, EATRIS & the TRISTAN Consortium (#IB4SD-116106) (2018)
PurposeThe aim of this study was to investigate the variability in quantitative performance and feasibility of quantitative harmonisation in Zr-89 PET/CT imaging.MethodsEight EANM EARL-accredited (Kaalep A et al., Eur J Nucl Med Mol Imaging 45:412-22, 2018) PET/CT systems were investigated using phantom acquisitions of uniform and NEMA NU2-2007 body phantoms. The phantoms were filled according to EANM EARL guidelines for [F-18]FDG, but [F-18]FDG solution was replaced by a Zr-89 calibration mixture. For each system, standard uptake value (SUV) accuracy and recovery coefficients (RC) using SUVmean, SUVmax and SUVpeak metrics were determined.ResultsAll eight investigated systems demonstrated similarly shaped RC curves, and five of them exhibited closely aligning recoveries when SUV bias correction was applied. From the evaluated metrics, SUVpeak was found to be least sensitive to noise and reconstruction differences among different systems.ConclusionsHarmonisation of PET/CT scanners for quantitative Zr-89 studies is feasible when proper scanner-dose calibrator cross-calibration and harmonised image reconstruction procedures are followed. An accreditation programme for PET/CT scanners would facilitate multicentre Zr-89 quantitative studies.
Keywords: Klinikai orvostan